Nurses' perception of empowerment and its relationship with organizational commitment and trust in teaching hospitals in Iran. (10th April 2019) - Gholami, Mohammad; Saki, Mandana; Hossein Pour, Amir Hossein
Abstract: Aim: The aim of the present study was to clarify the relationship between perception of job empowerment and organizational commitment and trust among nurses in teaching hospitals of Khorramabad (Iran). Background: Lack of power has been widespread among nurses in their workplaces due to uneven distribution of power among hospital staffs. Giving power to only a few individuals at the top of hospital hierarchy may often make nurses feel weak in their workplaces and causes reduction in the patients' quality care. Methods: This is a descriptive cross‐sectional study which included 160 officially employed nurses in four teaching hospitals of Khorramabad (west Iran) selected by stratified random sampling. The instruments used were: The Conditions of Work Effectiveness Questionnaire–II (C.W.E.Q‐II), which measures nurses' empowerment, the Pressure Management Indicator, which measures organizational commitment and the Trust in Management Scale, which measures organizational trust. The data were analysed by the SPSS software using the descriptive and analytic statistical tests employing chi‐square, Fisher's test and the Spearman–Brown correlation coefficient. Results: The results showed that the nurses had a below moderate score in their perception of job empowerment ( < ! [ C D A T A [ x ¯ ] ] > = 2.38 ± 0.70), with the highest score in their perception of access to "opportunity" subscale ( < ! [ C D A T A [ x ¯ ] ] > = 3.11 ± 0.95), and the lowest score in their perception of access to "formal power" ( < ! [ C D A T A [ x ¯ ] ] > = 2.43 ± 0.95). Additionally, moderate "organizational commitment" and "organizational trust" were reported with < ! [ C D A T A [ x ¯ ] ] > = 4.5 ± 0.90 and < ! [ C D A T A [ x ¯ ] ] > = 4.01 ± 1.11, respectively. The highest and the lowest perception scores were found for "continuous commitment" and "affective commitment" with < ! [ C D A T A [ x ¯ ] ] > = 4.94 ± 0.97 and < ! [ C D A T A [ x ¯ ] ] > = 4.26 ± 1.21, respectively. There were positive significant relationships between the three major variables of the study ( p < 0.001). Conclusion: The results showed that there was a positive and significant relationship between nurses' perception of job empowerment, organizational commitment and trust. Implications for nursing management: Nursing managers can increase the motivating factors among their nurses through evaluating organizational variables like empowerment and organizational trust. In fact, through recognition of the relationship between empowerment and organizational trust, one can design the interventions of structural empowering for the improvement of professional nursing practice, nurses' workplace well‐being and safe quality care.